POTENSI CACING TANAH EKSOTIK ENDOGEIK Pontoscolex corethrurus UNTUK PRODUKSI VERMIKOMPOS GRANUL (VERMIGRAN) BERBASIS BAHAN ORGANIK LOKAL - Widyatmani Sih Dewi; Sumarno Sumarno; Sri Rossati (Caraka Tani: Journal of Sustainable Agriculture, 2012)
The potential of Exotic Earth worm Endogeik (Pontoscolex corethrurus) for Production Vermikompos granules (Vermigran) Local Organil-Based Materials. In 2011, total demand for organic fertilizer in Indonesia was 12.394 million tons and 2.601 million tons of new available. This requirement will continue to increase until 2015, so the opportunity to develop great organic fertilizer. One disadvantage of the use of organic fertilizers is very much in volume (bulky), it is necessary vermikompos manufacturing innovation in the form of granules to be more efficient in the applicationand transport. Research objectives are: (1) study the potential of earthworms in producing vermikompos Pontoscolex corethrurus of l ocal organic ingredients, and (2)produce quality vermikompos in the form of granules. The study was conducted in a greenhouse Fak. Agriculture and in the yard of a house in Ngesrep, Boyolali, in July-November 2011. The study design using a Completely Randomized Design, factorial,two factor. Factor 1 is composed of three types of worms cedar, and the second factoris the variation of the type of organic material, consisting of 7 cedar. The variablesmeasured were vermikompos nutrient quality and speed of the water solubility vermikompos granules. The results showed that Pontoscolex corethrurus high potentialto produce vermikompos that meet ISO quality compost. Cow pile, pile quail, water hyacinth can be used as a raw material vermikompos. Clay, starch, starch and claymixture (1:1) can be used as an adhesive vermikompos granules (vermigran) soluble in water at <48 hours. Production vermigran great potential for developmentas a high-quality organic fertilizer.